Analisis Mutu pada Rantai Pasar Usaha Rumput Laut Eucheuma Spinosum di Desa Darawa Kecamatan Kaledupa Slatan Kabupaten Wakatobi - Febriani, Febriani; Awaluddin, Awaluddin; Januar Noor, Rahmat (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2023)
This study aimed to determine how the marketing chain of Eucheuma spinosum seaweed and the quality of dry Eucheuma spinosum seaweed originate from each marketing chain in the research area. This research was expected to provide information to the public regarding the marketing chain of dried Eucheuma spinosum seaweed. This research was held from July to August 2021 in Darawa Village, South Kaledupa District, Wakatobi Regency, and the Laboratory of Water Productivity and Quality, Faculty of Marine Science and Fisheries, Hasanuddin University. This type of research is quantitative and qualitative research (mixed method). The results showed that the seaweed market chain originating from Darawa Village, South Kaledupa District, Wakatobi Regency, consists of fishermen as producers, local collectors, interregional collectors, and intercity collectors. The results of the research on the quality of dry Eucheuma spinosum seaweed showed that the water content at the fishermen level was 62,212%, local collectors were 63,485%, and inter-regional collectors were 64,139%. The viscosity test value of dry Eucheuma spinosum seaweed at the fishermen level is 30.77 cps, local collectors are 34.57 cps, and inter-regional collectors are 32.40 cps. This research concludes that the seaweed from Darawa Village has penetrated the inter-regional market while the quality of the seaweed at each level of the market chain does not show a significant difference.